Influence of Nanosegregation on the Surface Tension of Fluorinated Ionic Liquids - Luis, Andreia
We have investigated, both theoretically and experimentally, the balance between the presence of alkyl and perfluoroalkyl side chains on the surface organization and surface tension of fluorinated ionic liquids (FILs). A series of ionic liquids (ILs) composed of 1-alkyl-3-methylimidazolium cations ([C(n)C(1)im] with n = 2, 4, 6, 8, 10, or 12) combined with the perfluorobutanesulfonate anion was used. The surface tensions of the investigated liquid salts are considerably lower than those reported for non fluorinated ionic liquids. The most surprising and striking feature is the identification, for the first time, of a minimum at n = 8 in the surface tension versus the length of the IL cation alkyl side chain. Supported by molecular dynamics (MD) simulations, it was found that this trend is a result of the competition between the two nonpolar domains (perfluorinated and aliphatic) pointing toward the gas-liquid interface, a phenomenon which occurs in ILs with perfluorinated anions. Furthermore, these ILs present the lowest surface entropy reported to date.